A Review of Novel Anticoagulants - Green, Jordan A.; Couban, Stephen; Anderson, David; Shivakumar, Sudeep (DALHOUSIE MEDICAL JOURNAL, 2013)
The well-established indications for anticoagulant therapy include atrial fibrillation, venous thromboembolism (VTE) and mechanical heart valves. Vitamin K antagonists are the most common anticoagulants used in the outpatient setting. Two new classes of anticoagulants (direct thrombin and factor Xa inhibitors) have shown promise as alternatives to the vitamin K antagonists. Specifically, dabigatran, rivaroxaban and apixaban have been studied in comparison to warfarin for their use in preventing systemic stroke/embolism in patients with atrial fibrillation and for managing the recurrence of VTE. This article will review the literature on the efficacy of these agents, as well as the benefits and disadvantages of their use.